Implementation of Health Communication for The Prevention and Transmission of Covid-19 in Communities in The Working Area of UPT Puskesmas Simpang Empat 1, Banjar District - Herman Faisal; Bayu Lintang; Marhaeni Fajar Kurniawati (Equivalent: Jurnal Ilmiah Sosial Teknik, 2023)
Health communication is used as an effort to prevent transmission of COVID-19. The problem is that until now the community does not know how to prevent the spread and break the chain of transmission of COVID-19. Researchers chose the practice of implementing health communication held in the work area of ​​UPT Puskesmas Simpang Empat 1, Banjar Regency, South Kalimantan Province for prevention and transmission through the COVID-19 health protocol. The research method used is a descriptive case study method. The object of his research is the practice of implementing health communication to prevent the transmission of COVID-19 by implementing the Adaptation of New Habits (IMR). The research results show that the implementation of health communication is influenced by three aspects, namely input, process and output. The risk-based health communication that has been carried out has proven to bring changes to the knowledge, attitudes and behavior of the community in dealing with the COVID-19 pandemic.